2020
DOI: 10.3390/nu12030819
|View full text |Cite
|
Sign up to set email alerts
|

Obesogenic Lifestyle and Its Influence on Adiposity in Children and Adolescents, Evidence from Mexico

Abstract: Overweight (OW) and obesity (OB) during childhood/adolescence are major public health problems in Mexico. Several obesogenic lifestyle (OL) risk factors have been identified, but the burden and consequences of them in Mexican children/adolescents remain unclear. The objective of this study was to estimate the prevalence of OL components and describe their relationships with adiposity, and OW/OB. A population-based cross-sectional study of Mexican children/adolescents with nutritional assessment, data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…With regard to sedentary and nutritional habits and despite the fact that 74⋅4 % of the participants in our studies performed <3 h of physical activity per week, no statistically significant differences were found in the nutritional status of the patients. This is a finding that is consistent with the one reported by Smetanina et al in Lithuania ( 18 ) , but it is different from what was reported in Brazil ( 25 , 36 , 37 ) , Mexico ( 38 ) , Australia ( 39 ) , Egypt ( 40 ) , Nigeria ( 33 ) , Nepal ( 31 ) , Iran ( 41 ) and among others ( 23 , 42 ) . The relationship between the educational level of the parents and the nutritional status of the children continues to be contradictory, because some studies have reported higher frequencies of overweight or obesity in children whose parents have a higher educational level ( 25 , 31 , 35 , 43 ) , yet, other studies associate less education with higher rates of overweight/obesity ( 18 ) .…”
Section: Discussionsupporting
confidence: 84%
“…With regard to sedentary and nutritional habits and despite the fact that 74⋅4 % of the participants in our studies performed <3 h of physical activity per week, no statistically significant differences were found in the nutritional status of the patients. This is a finding that is consistent with the one reported by Smetanina et al in Lithuania ( 18 ) , but it is different from what was reported in Brazil ( 25 , 36 , 37 ) , Mexico ( 38 ) , Australia ( 39 ) , Egypt ( 40 ) , Nigeria ( 33 ) , Nepal ( 31 ) , Iran ( 41 ) and among others ( 23 , 42 ) . The relationship between the educational level of the parents and the nutritional status of the children continues to be contradictory, because some studies have reported higher frequencies of overweight or obesity in children whose parents have a higher educational level ( 25 , 31 , 35 , 43 ) , yet, other studies associate less education with higher rates of overweight/obesity ( 18 ) .…”
Section: Discussionsupporting
confidence: 84%
“…Currently, obesity has a worldwide prevalence of 13% and overweight of 39% [3]. Olfaction in obesity: While the etiology of obesity is multifactorial, one of the main contributing factors driving this rapid increase is the obesogenic environment [4,5]. Our environment is full of energy-rich foods that are advertised via stimuli for all sensory channels.…”
Section: Introductionmentioning
confidence: 99%
“…Since obesity is a risk factor for many diseases such as diabetes type 2, cardiovascular diseases, certain forms of cancer and stroke (Rosenthal et al, 2017), it is essential to understand the factors that accompany excessive accumulation of body weight and its maintenance. One major factor driving the rapid increase of obesity is our obesogenic environment that encourages overconsumption of energy-dense foods even without physiological needs (Berthoud, 2012;Lopez-Gonzalez et al, 2020). Especially external cues, such as the smell of foods, can trigger appetite and intensify food cravings (Firmin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%